Staff Learning as it Relates to Student Learning: A Look at Effective Professional Development - Mcdonell, Zzachary (My University, 2024)
This culminating project studies and explores the effectiveness of professional development (PD) programs and their impact on long-term teaching practices and student learning outcomes. By synthesizing existing literature and examining various studies, the research identifies key factors contributing to PD efficacy, including targeted interventions, the importance of continuous engagement, and the role of teacher identity and growth mindset. The findings emphasize the value of diverse PD strategies and collaborative opportunities, highlighting that participation in PD activities, regardless of the level of involvement, yields positive outcomes. The study also underscores the dynamic nature of educators' engagement with PD across different career stages and the need for tailored PD programs that address these evolving needs. The research provides actionable insights for education leaders to design and implement flexible PD initiatives that enhance teacher performance and foster a culture of continuous improvement, ultimately benefiting student success.
Master of Education (MEd)
Keywords: professional development; teacher identity; community of practice; growth mindset